Heisenberg and the doctrine of colors of Goethe and Newton (Scientiae Studia, 2015)
This paper aims at exposing the Heisenberg's conference "The teachings of Goethe and Newton on colors in the light of modern physics", presented in 1941, whose translation is presented here. In the first place the paper analyzes the philosophical project of an ordination of the reality, developed by the physicist in the early 1940s and which is the basis for the discussion of the "Teachings of Goethe and Newton on colors". Secondly it exposes some philosophical implications of the quantum theory by emphasizing the point of view of the Copenhagen school. Finally, it shows how the dispute between Goethe and Newton is exploited to defend the abstractions of the theoretical physics against the attacks of the so called "German physicists" and, at the same time, to preserve the worth of the Goethe's intuitive analysis.